Customer Relationship Management for Third Party Logistic Company’s Competitiveness in Shanghai, China - Liang, Binyu (2016)
Nowadays, customer resource has become key resource and important intangible asset of the enterprise competition, at the same time meet the personalized needs of customers become the key to winning in the competition. This study is focus on the customer relationship management influences together with other key factors (information technology, customer knowledge management, corporate philosophy) to ascertain the level of relationship between CRM and the third party logistics companies’ competitiveness. The previous study is mainly focus on the general influences of customer relationship management, this study is mainly aim at customer relationship management and other key supporting factors will have an influence on the third party logistics companies’ competitiveness. The target population for this study is third part logistics companies in Shanghai, China and the sample size of the population that the researcher estimate to Cohen is 82 respondents. The study by online questionnaire collect data and using SPSS to validate the relationships among the structural variables in the theoretical model. This study expected to know the customer relationship management and other key supporting factors will have an influence on the third party logistics companies’ competitiveness and provide suggestions for third party logistics companies to improve their competitiveness by CRM.